Associations of glycemia and lipid levels in pregnancy with dyslipidemia 10–14 years later: The HAPO follow-up study. (March 2022) - Lowe, Lynn P.; Perak, Amanda M.; Kuang, Alan; Lloyd-Jones, Donald M.; Sacks, David A; Deerochanawong, Chaicharn; Maresh, Michael; Ma, Ronald C.; Lowe, William L.; Metzger, Boyd E; Scholtens, Denise M.; ,
Highlights: GDM was associated with dyslipidemia for all lipids 10–14 years later. Most GDM-dyslipidemia associations were independent of pregnancy lipid levels. GDM-dyslipidemia associations occurred without type 2 diabetes development. Abstract: Aims: To examine associations of pregnancy glycemia with future dyslipidemia. Methods: We analyzed data from Hyperglycemia and Adverse Pregnancy Outcome Follow-Up Study participants. We examined associations of gestational diabetes (GDM), sum of fasting, 1-hour, and 2-hour glucose z-scores after 75-g load, insulin sensitivity, and lipid levels at 24–32 weeks' gestation with dyslipidemia 10–14 years postpartum. Results: Among 4, 693 women, 14.3% had GDM. At follow-up, mean (SD) age was 41.7 (5.7) years, 32.3% had total cholesterol (TC) ≥ 5.17, 27.2% had HDL cholesterol < 1.29, 22.4% had LDL cholesterol (LDL-C) ≥ 3.36, 10.9% had triglycerides ≥ 1.69 mmol/L, and 2.9% had type 2 diabetes. After covariate adjustment, pregnancy glycemic measures were associated with all follow-up dyslipidemias. After additional adjustment for pregnancy lipids, GDM remained associated with TC ≥ 5.17 mmol/L (odds ratio [95% CI], 1.63 [1.22–2.18]) and LDL-C ≥ 3.36 mmol/L (1.63 [1.20–2.22]), even in the absence of type 2 diabetes development (1.55 [1.15–2.10] and 1.56 [1.13–2.16], respectively). Continuous glycemic measures in pregnancy were significantly associated with all follow-up dyslipidemias, independent of pregnancy lipids and type 2 diabetes. Conclusions: Pregnancy glycemia was associated with dyslipidemia 10–14 years later, independent of pregnancy lipid levels and in the absence of type 2 diabetes development. Lipid screening after GDM deserves special consideration.